The impact of segregation on wage inequality : a look at recruitment and pay policies at the firm level - Portela, Miguel (2001)
Wage dispersion within firms has increased, whilst segregation of workers according to their schooling level has also increased, as some firms "specialise" in workers with a high level of education and other "specialise" in workers with low level of education. This study analyses the interaction between the demand for education by firms and the wage in the Portuguese economy. A bivariate regression is implemented in wich the joint decision of the wage and education of the workers to be recruited is modelled. Some of the conclusions of the single-equation wage model are inverted, because that model captures a mixture of the firm's recruitment policy and the firm's wage policy. This is the case of the returns to experience and seniority. It is also observed that the increase in wage discrimination against women is more pronounced than captured by traditional uniequational model. The same occurs with the wage premium for education.